2022
DOI: 10.3390/vaccines10122026
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Vaccination Intention against COVID-19 Using Theory of Planned Behavior: A Systematic Review and Meta-Analysis

Abstract: This study systematically analyzed the literature using the theory of planned behavior (TPB) as a theoretical framework to examine the influence of its constructs on vaccination intention against COVID-19. Quantitative studies were searched in PubMed, CINAHL, Web of Science, and Google Scholar following the PRISMA guidelines. The average rate of COVID-19 vaccination intention was 73.19%, ranging from 31% to 88.86%. Attitude had the strongest association with vaccination intention (r+ = 0.487, 95% CI: 0.368–0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 104 publications
2
47
0
Order By: Relevance
“…In line with TPB postulations, our moderation analysis showed individuals who reported a higher perceived likelihood of contracting COVID-19 were more likely to express vaccine intent, which is consistent with other studies [ 20 , 23 , 42 , 43 ]. Interestingly, we also found sexual minority individuals with mild anxiety/depression symptoms had the highest likelihood of receiving the COVID-19 vaccine, but individuals with moderate and severe anxiety/depression had a lower likelihood of vaccination.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with TPB postulations, our moderation analysis showed individuals who reported a higher perceived likelihood of contracting COVID-19 were more likely to express vaccine intent, which is consistent with other studies [ 20 , 23 , 42 , 43 ]. Interestingly, we also found sexual minority individuals with mild anxiety/depression symptoms had the highest likelihood of receiving the COVID-19 vaccine, but individuals with moderate and severe anxiety/depression had a lower likelihood of vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…Presently, knowledge on COVID-19 vaccination uptake and attitudes among sexual minority populations is still developing. According to the Theory of Planned Behavior (TPB), an individual’s vaccine intention is likely to be influenced by their attitudes, subjective norms and beliefs, or perceived behavioral control over COVID-19 vaccination [ 23 ]. Furthermore, vaccination intentions can be modified by sociodemographic and mental health factors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding H1N1, the Theory of Planned Behavior has appeared to contribute to intended vaccination uptake in one study [ 60 ], predicted 60% of adults’ intention to receive an H1N1 vaccination in another study [ 61 ], and explained 70% of the variance in vaccination intention in another study [ 62 ]. Regarding COVID-19, a recent systematic review and meta-analysis investigated the role of Theory of Planned Behavior constructs in determining intention to get vaccinated against COVID-19 [ 63 ]. The findings of this meta-analysis revealed that the COVID-19 vaccination intention rate was relatively high at 73%.…”
Section: Introductionmentioning
confidence: 99%
“…Socio-demographic variables, psychological factors, vaccine hesitancy, COVID-19 related variables, personal beliefs, knowledge, fear, conspiracy theories, fake news, and trust are the most important factors that influence individuals' decision to accept the COVID-19 vaccines. [17][18][19][20][21][22] New SARS-CoV-2 variants are emerged and COVID-19 is still a public health issue especially for vulnerable groups such as people with chronic medical conditions. Thus, vaccination uptake against COVID-19 among high-risk groups should be maintained in high levels in order to avoid the negative consequences of the disease.…”
Section: Introductionmentioning
confidence: 99%